?We All Have Strengths?: A Retrospective Qualitative Evaluation of a Resilience Training for Latino Immigrants in Philadelphia, PA - Jamile Tellez Lieberman; Krystal Lobban; Zujeil Flores; Kristin Giordano; Emily Nolasco-Barrientos; Yoshiaki Yamasaki; Ana P. Martinez-Donate (Mary Ann Liebert, 2019)
Background: Limited research has explored sources of resilience for Latino immigrants or the potential of resilience-based interventions to promote Latino immigrant health and well-being. Purpose: To evaluate Latino immigrants' experiences with a resilience training and application of the training to participants' personal lives and their communities among Latino immigrants. Methods: We conducted a retrospective, qualitative study in Philadelphia, PA from 2017 to 2018. We completed semi-structured, key informant interviews with nine participants who had taken the resilience training, and one facilitator (N=10). Transcripts were analyzed via interpretive content analysis. Results: The training resonated deeply with participants because of their personal traumas and immigration-related adversity. Participants were primed by past experiences of violence, as well as by daily struggles they encounter as Latino immigrants in the United States amid worsening anti-immigrant rhetoric and policy. The training was found to be transformative by allowing participants to discover and tap into their own inherent resilience. Participants utilized the knowledge and skills acquired from the training to better manage daily situations, as well as worked to strengthen others within their networks. Conclusions: Resilience-based interventions can help to strengthen communities against adversity. Cultivating resilience in Latino immigrants can have positive effects on psychosocial health. Resilience-building approaches could be implemented as stand-alone or enhancing components of more complex health promotion interventions. More research is needed on resilience, as well as its utility in community-based interventions to promote the health and well-being of Latino immigrants.